A descriptive study on the resistance pattern of coagulase-negative staphylococci isolated from positive blood culture samples in a tertiary care hospital, Kolkata - Singh, Laishram Thanil; Das, Debalina; Chakrabarty, Partha Sarathi (Asian Journal of Medical Sciences, 2025)
Background: Blood cultures are needed to establish the diagnosis of bloodstream infections and are useful in directing appropriate antimicrobial therapy. Coagulase-negative staphylococci (CoNS) are among the most frequently isolated pathogens in blood cultures and an important cause of nosocomial bloodstream infections that are typically resistant to multiple antibiotics. The infection caused by CoNS is increasing as the number of artificial devices and catheters being inserted through skin become higher. Another concern is the rising occurrence of methicillin-resistant-CoNS (MR-CoNS) in hospitalized patients. Aims and Objectives: The aim of the study was to identify the species of CoNS along with their antimicrobial resistance pattern of the isolated CoNS from positive blood culture samples. Materials and Methods: A record-based descriptive study conducted in the Department of Microbiology, College of Medicine and Sagore Dutta Hospital. The study includes only the record of positive blood culture samples isolated with CoNS from admitted patients, sent for culture and susceptibility testing to the Microbiology department from July 1st, 2022, to June 30th, 2024. Results: A total number of 1080 blood culture samples were tested. 44 CoNS was isolated (in paired sample) out of 150 positive blood culture samples. The predominant isolates were Staphylococcus haemolyticus (45%) followed by Staphylococcus epidermidis (32%). 35 (80%) CoNS strains were resistant to Methicillin (MR-CoNS). Maximum (44%) CoNS were isolated from critical care unit blood culture samples. Conclusion: This study also showed a high prevalence of MR-CoNS. It should be kept in mind that patients suffered from CoNS isolates in their blood samples should be carefully evaluated before instituting therapy to avoid unnecessary use of antibiotics and also necessitating judicial and rational use of antibiotics to prevent an increase of resistance patterns and the emergence of MR-CoNS species along with the preventive measures to reduce the spread of virulent CoNS. This study also underscores the urgent need for effective infection control measures and antibiotic stewardship in combating antimicrobial resistance among CoNS in tertiary care hospitals.